Relasi Kuasa Identitas Etnis Dilembaga Legislatif Periode 2014-2019 (Studi Kasus Anggota DPRD Etnis Bugis Dikabupaten Indragiri Hilir, Provinsi Riau) - Hapsa, Hapsa; Purnomo, Eko Priyo (Journal of Governance and Public Policy, 2016)
Bugis ethnic group who live in Indragiri Hilir an ethnic immigrants, with the number of 150 816 inhabitants, ranks thirdafter the ethnic Malay and Banjar. However, ethnic Bugis able menjalain power relations appropriately. Evidenced bythe position of ethnic Bugis located in strategic places Inhil got various fields, especially in the legislature. This studyused a descriptive approach, the data collection technique interview legislators who are ethnic Bugis and othersteakholders. Power relation with the theoretical approach of the reproductive power Pierre Bourdieu, showed thatthe participant a the very keeping and maintaining ethnic identity inherited from their ancestors, so that they are ableto create habitus attached to its identity, as well as the domains and symbolic capital gained by establishing a relationshiptogether political parties, ethnic Java and regional organizations